A natural outbreak of infectious spleen and kidney necrosis virus threatens wild pearlspot, Etroplus suratensis in Peechi Dam in the Western Ghats biodiversity hotspot, India. Issue 5 (8th March 2022) - Swaminathan, Thangaraj Raja; Johny, Tina Kollannoor; Nithianantham, Sundar Raj; Sudhagar, Arun; Pradhan, Pravata Kumar; Sulumane Ramachandra, Krupesha Sharma; Nair, Reshma R.; Sood, Neeraj
Abstract: A large‐scale mortality of pearlspot, Etroplus suratensis was reported from Peechi Dam, an artificial tropical lake made for irrigation and drinking water supply in Kerala, India during 2018. This dam is located in the premises of Western Ghats, recognized as one of the biodiversity hotspots of the world. The objective of this study was to identify the aetiological agent of this large‐scale mortality of E. suratensis by systematic diagnostic investigation and identification of the pathogen. Virus isolation was carried out on a species‐specific pearlspot fin (PSF) cell line. Infected PSF cells showed cytopathic effects (CPEs) like cell shrinkage, rounding, enlargement, clustering, and subsequent detachment of cells with a high viral titre of 10 6⋅95 TCID50 ml −1 at 8 days post‐inoculation (dpi). Histopathological examination of the fish showed the presence of numerous abnormal enlarged basophilic cells and intracytoplasmic eosinophilic inclusions in the liver. Moreover, transmission electron microscopy (TEM) analysis revealed the presence of large numbers of 125–132 nm viral particles in the spleen tissues. PCR amplification and phylogenetic analysis of the major capsid protein (MCP) gene sequence confirmed that the causative agent was infectious spleen and kidney necrosis virus (ISKNV) of the genus Megalocytivirus . The experimental infection recorded 86.7 ± 2.7% mortality in the E. suratensis (body weight 11.01 ± 2.7 g; body length 8.01 ± 2.23 cm) injected with 1 × 10 4⋅25 TCID50 ml −1 ISKNV per fish. Our detailed investigation provided definitive diagnosis of ISKNV in the severe mass mortality event in wild E. suratensis in Peechi Dam, India, adding one more species to expanding host range of ISKNV infection. The high mortality rate of ISKNV infection in pearlspot suggests the perilous nature of this disease, particularly among the wild fish population.